Corporate strategy in a transitional economy : a study of Maya cement in Hangzhou, Zhejiang, PRC - Gan, Ling Horng (2008)
Postulate a strategic framework relevant to competitive industries in a transitional economy through an understanding of Hangzhou Maya Cement Co., Ltd. and Hangzhou Maya Dragon Cement Co., Ltd. and their business operations in Zhejiang, People’s Republic of China.